2014
DOI: 10.1088/0741-3335/56/9/095024
|View full text |Cite
|
Sign up to set email alerts
|

The effect of toroidicity on reversed field pinch dynamics

Abstract: The influence of the curvature of the imposed magnetic field on Reversed Field Pinch dynamics is investigated by comparing the flow of a magnetofluid in a torus with aspect ratio 1.83, with the flow in a periodic cylinder. It is found that an axisymmetric toroidal mode is always present in the toroidal, but absent in the cylindrical configuration. In particular, in contrast to the cylinder, the toroidal case presents a double poloidal recirculation cell with a shear localized at the plasma edge. Quasi-single-h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 44 publications
2
14
0
Order By: Relevance
“…The dominant velocity mode corresponds to n ¼ 6 for the present case, and an important n ¼ 0 subdominant velocity mode is observed, as was shown in Ref. 6. It is the n ¼ 6 velocity structure, flowing in both toroidal directions, which sustains-at long-times-the modified axisymmetric magnetic field typical of RFP dynamics.…”
Section: B Kinetic and Magnetic Energy And Dissipationsupporting
confidence: 81%
See 2 more Smart Citations
“…The dominant velocity mode corresponds to n ¼ 6 for the present case, and an important n ¼ 0 subdominant velocity mode is observed, as was shown in Ref. 6. It is the n ¼ 6 velocity structure, flowing in both toroidal directions, which sustains-at long-times-the modified axisymmetric magnetic field typical of RFP dynamics.…”
Section: B Kinetic and Magnetic Energy And Dissipationsupporting
confidence: 81%
“…4 and 5. And, even though the curvature of the magnetic field induces effects absent in cylindrical geometry, 6 recent studies in cylindrical geometry show some agreement with experiments. 7,8 To study tokamaks, MHD has also been widely applied, see, for instance, Refs.…”
mentioning
confidence: 76%
See 1 more Smart Citation
“…In all simulations, we will consider the RFP regime where the magnetic geometry is self-organized into a helical structure. Typical similations using the same code and set-up are reported in 24 .…”
Section: A Numerical Set-upmentioning
confidence: 99%
“…The spontaneous spin-up of plasma in toroidal geometries using the viscousresistive MHD equations has been discovered in Morales et al [24]. The effect of toroidicity in reversed field pinch devices is studied in [26]. Roberts et al [35] investigated helically forced MHD flows in cylindrical geometries and showed the persistence of helical modes even when the dynamics becomes turbulent A penalty method for hyperbolic partial differential equations modeling the edge plasma transport in a tokamak has been proposed in [2].…”
Section: Introductionmentioning
confidence: 99%